Interspecific interaction between Telenomus remus (Hymenoptera: Platygastridae) and Trichogramma pretiosum (Hymenoptera: Trichogrammatidae) on Spodoptera frugiperda (Lepidoptera: Noctuidae) eggs - Tatiana R. Carneiro; Odair A. Fernandes (Anais da Academia Brasileira de Ciências, 2012)
This work aimes to evaluate the interspecific interaction between Trichogramma pretiosum and Telenomus remus, two biological control agents of fall armyworm (Spodoptera frugiperda) eggs. Eggs of Spodoptera frugiperda previously parasitized by Telenomus remus were offered to Trichogramma pretiosum, and those parasitized by Trichogramma pretiosum were offered to Telenomus remus. The previously parasitized eggs were tested at different embryonic development stages for each parasitoid. In addition, to evaluate the competition between species, Spodoptera frugiperda eggs were offered to the parasitoids simultaneously. The behavior of the insects was recorded under a stereomicroscope. When Spodoptera frugiperda eggs were previously exposed to either parasitoid, there was no emergence of the other parasitoid. When the Telenomus remus and Trichogramma pretiosum females were placed together with Spodoptera frugiperda eggs, Telenomus remus had a greater parasitism rate. Except searching time, all Trichogramma pretiosum behaviors took a longer time than Telenomus remus behaviors. Thus, despite belonging to different families, each of these parasitoids is able to recognize host eggs previously parasitized by the other. So, this suggests that the recognition mechanism involved is not exclusively specific. Este trabalho objetiva avaliar a interação interesespecífica entre Trichogramma pretiosum e Telenomus remus, dois agentes de controle biológico de ovos de Spodoptera frugiperda. Posturas de Spodoptera frugiperda previamente parasitadas por Telenomus remus foram ofertadas a Trichogramma pretiosum e aquelas parasitadas por Trichogramma pretiosum foram ofertadas a Telenomus remus. As posturas previamente parasitadas foram testadas em diferentes estágios de desenvolvimento embrionário para cada parasitoide. Ainda para verificar a competição entre as espécies, posturas de Spodoptera frugiperda foram ofertadas aos parasitoides simultaneamente. O comportamento dos insetos foi observado sob microscópio estereoscópico. Quando as posturas de Spodoptera frugiperda foram previamente expostas a qualquer um dos dois parasitoides, não houve emergência do outro parasitoide. Quando as fêmeas de Telenomus remus e de Trichogramma pretiosum foram colocadas juntas com as posturas de Spodoptera frugiperda, Telenomus remus apresentou maior taxa de parasitismo. Com exceção do tempo de busca, todos os comportamentos de Trichogramma pretiosum foram mais demorados do que os de Telenomus remus. Portanto, apesar de pertencerem a famílias diferentes, cada um desses parasitoides pode reconhecer ovos de hospedeiro previamente parasitados pela outra espécie. Este fato sugere que o mecanismo de reconhecimento envolvido não é exclusivamente específico.